2007
DOI: 10.1039/b617871e
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine containing oligonucleotides for the development of metallodeoxyribozymes

Abstract: Novel transition metal catalysts based on oligonucleotides can be easily obtained by functionalization of 5-iodouridine with phosphine ligands, resulting in good asymmetric induction in palladium catalyzed allylic nucleophilic substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 23 publications
0
30
0
2
Order By: Relevance
“…Bonding distances and angles are similar to those found in a related compound reported by us. [10] In spite of that, 7m presents a more open structure than 7o, with the diphenylphosphane unit displaced far away from the ribose ring and the electron pair at the phosphorus atom pointing outwards the molecule. This conformation is probably enforced by an in-tramolecular hydrogen bond between the OH at the 5' position of the ribose ring and the carbonyl oxygen atom of the amide group.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Bonding distances and angles are similar to those found in a related compound reported by us. [10] In spite of that, 7m presents a more open structure than 7o, with the diphenylphosphane unit displaced far away from the ribose ring and the electron pair at the phosphorus atom pointing outwards the molecule. This conformation is probably enforced by an in-tramolecular hydrogen bond between the OH at the 5' position of the ribose ring and the carbonyl oxygen atom of the amide group.…”
Section: Resultsmentioning
confidence: 97%
“…[3][4][5] Several research groups have combined the molecular recognition of proteins with transition metal catalysis [6][7][8] and in more recent years the focus has also spread to the use of DNA combined with transition metals. Two methods have been used to attach transition metal fragments to DNA: they are the covalent [9][10][11] and non covalent [12][13][14][15][16] approaches. Both Jäschke [9] and Roelfes and Feringa [17] groups have found that the catalytic results were sequence dependent.…”
Section: Introductionmentioning
confidence: 99%
“…[54] A significant influence of the solvent was found on the enantioselectivity, with ee changing from 80 % (S) in tetrahydrofuran (THF) to 16 % (R) in a 50:50 mixture of acetonitrile and THF for R 1 = R 2 = H. For R 1 = R 2 = Ac the ee switched from 8 % (S) in THF to 23 % (R) in dichloromethane. Disappointingly, a trimer containing the phosphane-modified nucleotide gave lower enantioselectivities (< 12 % ee).…”
Section: Phosphane-modified Dnamentioning
confidence: 96%
“…[60] The groups of Kazlauskas [61] and Soumillion [62] simultaneously reported the replacement of the zinc atom in the active site of carbonic anhydrases with manganese, leading Scheme 11. Phosphane-modified mono-and trinucleotides used in palladium-catalysed asymmetric allylic amination: a) mononucleotide inserted in trinucleotides, [54] b) mononucleotide inserted into 15-base-long oligonucleotides. [56] to an artificial metalloenzyme for asymmetric epoxidation reactions.…”
Section: Dative Anchoringmentioning
confidence: 99%
“…However, covalent modification of DNA is laborious and very time consuming, which complicates the catalyst optimization process. This is illustrated by the fact that several approaches to the synthesis of ligand-DNA conjugates have been reported, [36][37][38] but in only a few cases successful catalysis have been achieved.…”
Section: Helical Polymers That Do Not Contain Chiral Side Chainsmentioning
confidence: 99%